Evaluating response strategies to deal with Negative Word-of-Mouth on Facebook pages of Telecommunications Operators in Portugal - Silva, Raquel Maria Martins Carneiro da (2019)
The Telecommunications represent one of the leading industries in Portugal when it comes to complaints and Negative Word-Of-Mouth (NWOM), including online NWOM. Providing efficient answers, basing them on an adequate response strategy, is one possible form of complaint management. The goal is then to understand if an alternative response strategy could be applied, in order to deal with NWOM posted online by costumers, so that it could impact the intentions and opinions of other customers – who are exposed to this type of content. An extensive comparison between the current response strategy applied and what the existing literature suggests was made, so that an actual alternative response strategy could be proposed. Later, an online questionnaire was created, as it was essential to develop an experimental in-between groups design. One group (A) was exposed to the current response strategy; while the other (B) was exposed to the alternative one proposed. Questions concerning customers’ opinions and intentions based on the three constructs proposed – Brand Attitude, Repatronage and Repurchase Intentions and NWOM Intention – were included. The main conclusion obtained was that no improvements concerning customers’ intentions were reached, by applying the alternative response strategy proposed. The three formulated hypotheses – associated with the three proposed constructs – were rejected, as no statistically significant difference (between the two groups) was found. By exploring and proposing a concrete alternative response strategy, the current research adds not only academic but also managerial value. To conclude, relevant limitations are discussed and future research orientations are proposed.